2022
DOI: 10.1200/jco.2022.40.16_suppl.3518
|View full text |Cite
|
Sign up to set email alerts
|

Plasma RAS dynamics and anti-EGFR rechallenge efficacy in patients with RAS/BRAF wild-type metastatic colorectal cancer: REMARRY and PURSUIT trials.

Abstract: 3518 Background: Rechallenge with anti-EGFR monoclonal antibody (EGFR mAb) showed certain activities in patients (pts) with RAS/ BRAF V600E wild-type (wt) metastatic colorectal cancer (mCRC), particularly in pts with negative plasma RAS (p RAS) mutation by circulating-tumor DNA (ctDNA) assay at ‘just before’ the rechallenge therapy. However, the efficacy is unknown in pts with RAS/ BRAF wt mCRC whose p RAS was converted to positive once during or after EGFR mAb. Therefore, we conducted REMARRY, a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Recently, Parseghian et al also reported that patients who responded to panitumumab as an anti‐EGFR rechallenge therapy had a longer median interval from prior anti‐EGFR therapy than those nonresponders 4 . In the PURSUIT study, 5 rechallenge with panitumumab and irinotecan resulted in a higher confirmed ORR of 37.5% in patients with a longer anti‐EGFR‐free interval (>365 days) than in those with a shorter interval (<365 days, ORR: 9.5%, P = .0037). Consistent with the observation of previous studies, patients with longer (>365 days) intervals show an increased probability of obtaining a clinical benefit from this anti‐EGFR retreatment with an ORR of 33.3% and a median PFS of >8 months in the overall evaluable population as well as in the subgroup of prior responders, in contrast with those with shorter interval (<365 days, ORR: 20.0%, mPFS: 4.7 months in the overall population; ORR: 16.7%, mPFS: 3.3 months in prior‐responders).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Parseghian et al also reported that patients who responded to panitumumab as an anti‐EGFR rechallenge therapy had a longer median interval from prior anti‐EGFR therapy than those nonresponders 4 . In the PURSUIT study, 5 rechallenge with panitumumab and irinotecan resulted in a higher confirmed ORR of 37.5% in patients with a longer anti‐EGFR‐free interval (>365 days) than in those with a shorter interval (<365 days, ORR: 9.5%, P = .0037). Consistent with the observation of previous studies, patients with longer (>365 days) intervals show an increased probability of obtaining a clinical benefit from this anti‐EGFR retreatment with an ORR of 33.3% and a median PFS of >8 months in the overall evaluable population as well as in the subgroup of prior responders, in contrast with those with shorter interval (<365 days, ORR: 20.0%, mPFS: 4.7 months in the overall population; ORR: 16.7%, mPFS: 3.3 months in prior‐responders).…”
Section: Discussionmentioning
confidence: 99%
“…23 Recently, Parseghian et al also reported that patients who responded to panitumumab as an anti-EGFR rechallenge therapy had a longer median interval from prior anti-EGFR therapy than those nonresponders. 4 In the PURSUIT study, 5 rechallenge with panitumumab and irinotecan resulted in a higher confirmed ORR of 37.5% in patients with a longer anti-EGFR-free interval (>365 days) than in those with a T A B L E 3 Treatment-related adverse events (TRAEs). In addition to efficacy, toxicity is the most important factor in choosing third-line or later-line therapies.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…However, data from two additional prospective studies presented at the 2022 ASCO Meeting reported a less-than-expected ORR of 15% and 20% for blood-based rechallenge with anti-EGFR therapy, even in patients without any acquired resistance mutations. 24,25 More interestingly, recently available data looked at the optimal timing for EGFR-directed rechallenge, suggesting that eight months (corresponding to two half-lives) could reasonably be the best time for reintroducing this treatment strategy in the path of RAS-wild-type mCRC. 16 In our study, the patient population was consistent with the standard population of pretreated mCRC since all patients were exposed to both oxaliplatin and irinotecan in previous lines.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with an EGFR antibody-free interval of over 1 year had a significantly higher ORR (44.4% versus 7.3%, p = 0.0037). 45 The ongoing FIRE-4 phase III randomized controlled trial (RCT) will compare the efficacy of re-challenge cetuximab-chemotherapy treatment with regorafenib in the third-line setting, following disease progression after first-line cetuximab plus FOLFIRI and second-line bevacizumab plus FOLFOX (NCT02934529).…”
Section: Egfr Inhibitionmentioning
confidence: 99%